Effects of a Fluctuating Carrying Capacity on the Generalized Malthus-Verhulst Model - Héctor Calisto; Kristopher J. Chandía; Mauro Bologna (Advances in Mathematical Physics)
We consider a generalized Malthus-Verhulst model with a fluctuating carrying capacity and we study its effects on population growth. The carrying capacity fluctuations are described by a Poissonian process with an exponential correlation function. We will find an analytical expression for the average of a number of individuals and show that even in presence of a fluctuating carrying capacity the average tends asymptotically to a constant quantity.